Production of an ultrasound-assisted biosurfactant postbiotic from agro-industrial wastes and its activity against Newcastle virus - Behzadnia, Asma; Moosavi-Nasab, Marzieh; Mohammadi, Ali; Babajafari, Siavash; Tiwari, Brijesh K. (Frontiers in Nutrition, 2022)
The objective of this study is to optimize the biosurfactant production by Lactobacillus plantarum ATCC 8014 using low-cost substrates from industrial sources applying ultrasonication at 28 kHz frequency (power of 100 W). Given this, whey permeate and sugar cane molasses were screened to continue optimization using a central composite design to improve the production. Then, the effect of ultrasound was examined at different stages of microbial growth. The combination of whey permeate and sugar cane molasses with yeast extract (2.4 g/L) and inoculum size of 4.8 % for 26 h of fermentation time significantly influenced biosurfactant production by reducing the surface tension of water (41.86 mN/m). Moreover, ultrasonication led to the further reduction in surface tension value (39.95±0.35 mN/m). Further, no significant differences were observed between products from synthetic and waste-based media. The biosurfactants exhibited antiviral activity against Newcastle disease virus (NDV) LaSota strain. It was discovered that low-cost biosurfactant with a significant antiviral effectiveness can be used to develop commercial application instead of chemical surfactants and biosurfactants from expensive synthetic media.